In vitro anti leishmanial activity of selected medicinal plants in Ghana - Anning, Alberta Serwah (University of Cape Coast, 2016)
Leishmaniasis is a parasitic infection that affects mostly tropical and sub-tropical regions of the world and caused by diverse pathogens that belong to the genus Leishmania. The pentavalent antimonials developed in 1945 are still first line treatment drugs for both cutaneous and visceral leishmaniasis while amphotericin B is a second line treatment drug. These treatments come with toxic side effects even at effective doses and the lack of vaccine demand the urgent need for new anti leishmanial agents. This study aimed at investigating four plants used traditionally to treat parasitic infections. The collected plant parts were washed, dried, powdered and then extracted using ethanol. Different concentrations of the extracts ranging from 15.6 to 500 µg/mL in 0.1 % DMSO with M199 and a positive control of Amphotericin B were prepared in triplicates in 24-well plates that contained 117,000 parasites/well. The plates were incubated at 25 °C and promastigotes counted on 8, 12, 24 and 48 hours after incubation. Phytochemical screening on all crude extracts revealed the presence of steroids, triterpenoids, tannins, anthraquinons, saponins, alkaloids, flavonoids and glycosides. Of the four plants, Erythrophleum ivorense gave the best activity with an IC50 of 6.3 µg/mL after 72 hours. This was followed by C. oxycarpum, A. aubryanum and A. ahia respectively. Three compounds have been isolated from E. ivorense; erythroivorensin, eriodictyol and betulinic acid, with IC50s of 0.5, 61.8 and 247 µg/mL correspondingly on the promastigotes of L. donovani.
xv, 132p, ill.
Keywords: erythroivorensin; eriodictyol; betulinic acid; Amphotericin B; Pentamidine; leishmanicidal; promasigotes; Cutaneous leishmaniasis